Core outcome set for uncomplicated acute appendicitis in children and young people. Issue 8 (17th March 2020) - Sherratt, F. C.; Allin, B. S. R.; Kirkham, J. J.; Walker, E.; Young, B.; Wood, W.; Beasant, L.; ,; Eaton, S.; Hall, N. J.
Abstract : Background: Research studies to inform clinical practice and policy in children and young people with appendicitis are hampered by inconsistent selection and reporting of outcomes. The aim of this study was to develop a core outcome set for reporting all studies of uncomplicated acute appendicitis in children and young people. Methods: Systematic literature reviews, qualitative interviews with parents and patients treated for uncomplicated acute appendicitis, and a Study‐Specific Advisory Group informed a long list of outcomes. Outcomes were then prioritized by stakeholders based in the UK (patients, parents, and paediatric and general surgeons) in an online three‐round Delphi consensus process, followed by face‐to‐face consensus meetings. Results: A long list of 40 items was scored by 147 key stakeholders in the first Delphi round, of whom 90 completed the two subsequent Delphi rounds. The final core outcome set comprises 14 outcomes: intra‐abdominal abscess, reoperation (including interventional radiology procedure), readmission to hospital, bowel obstruction, wound infection, antibiotic failure, wound complication, negative appendicectomy, recurrent appendicitis, death, patient stress/psychological distress, length of hospital stay, time away from full activity and child's quality of life. Conclusion: A core outcome set comprising 14 outcomes across five key domains has been developed for reporting studies in children and young people with uncomplicated acute appendicitis. Further work is required to determine how and when to measure these outcomes. Abstract : Acute appendicitis in children and young people has a variety of outcomes reported. A core outcome set has been developed with paediatric and general surgeons, parents and patients. The core outcome set comprises 14 outcomes and should allow uniform reporting of outcomes that are important for key stakeholder groups. Fourteen key outcomes across five domains Abstract : Antecedentes: Los estudios de investigación que sirvan de base para la práctica clínica y la política en niños y adultos jóvenes con apendicitis se ven obstaculizados por inconsistencias en la selección y descripción de los resultados. El objetivo de este estudio fue desarrollar un conjunto central de resultados para todos los estudios de apendicitis aguda no complicada en niños y adultos jóvenes. Métodos: Para establecer una lista de resultados se efectuaron revisiones sistemáticas de la literatura, entrevistas cualitativas con padres y pacientes tratados por apendicitis aguda no complicada, y consulta con un Grupo de Asesoramiento Específico para el Estudio. Seguidamente, los resultados se priorizaron de acuerdo con los intereses de las partes interesadas (pacientes, padres, y cirujanos pediátricos y generales) en el Reino Unido a través de un proceso de consenso Delphi de tres rondas en Internet, seguido de reuniones personales de consenso. Resultados: Un total de 147 participantes puntuaron una larga lista de 40 ítems en la primera ronda Delphi, de los cuales 90 completaron las dos rondas Delphi subsiguientes. El conjunto final incluye 14 resultados: absceso intra‐abdominal, reoperación (incluyendo procedimientos radiológicos intervencionistas), reingreso, obstrucción intestinal, infección de herida, otras complicaciones de la herida, fracaso del tratamiento con antibióticos, apendicectomía blanca, apendicitis recidivante, muerte, estrés del paciente/sufrimiento psicológico, duración de la estancia hospitalaria, tiempo alejado de todas sus actividades y calidad de vida. Conclusión: Se ha desarrollado un conjunto central de resultados que incluye 14 resultados en cinco dominios clave para la descripción de estudios en niños y adultos jóvenes con apendicitis aguda no complicada. Se requieren más trabajos para determinar cómo y cuándo conviene medir estos resultados.